Cirurgia mamária em mulheres com câncer de mama metastático. Revisão sistemática Cochrane e metanálise - Tosello, Giuliano Tavares [UNIFESP] (2018)
Objective: To evaluate the efficacy of breast surgery in patients with metastatic breast cancer. Methods: A systematic review was conducted according to the Cochrane methodology. The electronic search was performed on February 22, 2016, using the MeSH terms "breast neoplasms", "mastectomy" and "analysis, survival" in the following electronic databases: the Cochrane Breast Cancer Specialized Register, CENTRAL, MEDLINE (by PubMed), EMBASE (by OvidSP), LILACS, ClinicalTrials.gov and the WHO International Clinical Trials Registry Platform. Hand search on citation reference lists and contact with study authors to identify additional studies completed the search procedures. Randomized clinical trials with women diagnosed with metastatic breast cancer, comparing breast surgery associated with systemic therapy versus systemic therapy, were included. Two independent researchers evaluated the studies obtained in the electronic search regarding the eligibility criteria and the risk of bias. The risk of bias in the included studies was assessed by the Cochrane Risk of Bias tool. The quality of the evidences was evaluated using the GRADE tool. The risk ratio (RR) was used to measure the treatment effect for dichotomous outcomes, mean differences (MD) for continuous outcomes, and risk ratio (HR) for timetoevent outcomes. Confidence intervals of 95% (95% CI) were calculated for these measures. The primary outcome was overall survival and quality of life. Secondary outcomes were progressionfree survival (local and distance control), breast cancerspecific survival and toxicity from local therapy. Results: Two randomized clinical trials involving 624 participants were included. Breast surgery did not improve the overall survival of women with metastatic cancer (HR = 0.83, 95% CI 0.531.31, very lowquality evidence), but the progressionfree survival site was 78% better (HR = 0.22, 95% CI 0.08 0.57, low quality evidence), and metastatic progressionfree survival worsened by 40% (HR 1.42, 95% CI 1.081.86, moderate quality evidence). Conclusion: Based on poor quality evidence from two randomized clinical trials, it is not possible to reach definitive conclusions about the risks and benefits of breast surgery in women with metastatic breast cancer.